Wpływ wielkoskalowego pożaru na skład pokarmu uszatki Asio otus - Gryz, Jakub; Krauze-Gryz, Dagny (Leśne Prace Badawcze, 2024)
In April 2020, a large-scale fire occurred in the Biebrza National Park (north-eastern Poland). Over 5,500 ha of meadows and forests were burned. In this study, we show how wildfire affected the diet of the long-eared owl Asio otus . We collected owl pellets in the Wroceń Forest in the central part of the burned area in the fall of 2020, several months after the fire, and then two years after the fire in 2022–2023. We also collected pellets of this owl species outside the burned area in the fall of 2020. Analysis of the pellets revealed that the diet of owls in the post-fire areas was much more diverse than that of owls in the unburned areas or in the same area but two years after the fire. The food niche of the owls in the burned areas was broader; in particular, they fed less frequently on their main prey (the root vole Microtus oeconomus ) and more frequently on other rodents, soricomorphs, birds, reptiles, amphibians, and insects. Our results showed that this owl species switched to a variety of other prey when M. oeconomus rapidly disappeared due to an extensive fire. The burned area could serve as a suitable hunting site because of the reduced plant cover. Thus, small animals that survived or recolonized burned areas could be easy prey for long-eared owls.